Utilisation of Radio Suara Surabaya as a traffic information medium in Indonesia - Huda, Anam Miftakhul; Rachmanda, Arvian Bhakti (Faculty of Communications Science, Dr. Soetomo University, 2025)
Radio media still play an important role as a source of public information, especially in conveying real-time traffic conditions. However, in today's digital era, the question arises as to how relevant the traffic congestion information conveyed by radio still is to the public. This study refers to the uses and gratifications theory, which emphasises that audiences choose media based on their ability to meet information needs. This study uses a quantitative approach with a survey method of 300 respondents, namely private vehicle users in Surabaya and its surroundings. The analysis focuses on the dimensions of accuracy, relevance, novelty of information, and listener loyalty. The results show that accurate, relevant, and up-to-date information about traffic conditions has a significant effect on continued listening. In addition, social interaction through the